Long non-coding RNA DANCR, a prognostic indicator, promotes cell growth and tumorigenicity in gastric cancer - Yan-Ping Hao; Jing-Hui Qiu; Dong-Bo Zhang; Cheng-Gong Yu (Tumor Biology)
Gastric cancer remains the third leading cause of cancer-related mortality worldwide, and proliferation of gastric cancer represents the major reason for its poor prognosis. Recent evidence indicates that long non-coding RNAs play crucial roles in development and progression of gastric cancer. Long non-coding RNA differentiation antagonizing non-protein coding RNA is upregulated in hepatic cell carcinoma, but the role of lncRNA differentiation antagonizing non-protein coding RNA in gastric cancer has not been explored. In this article, we found that differentiation antagonizing non-protein coding RNA is also upregulated in gastric cancer. Experiments revealed that silencing differentiation antagonizing non-protein coding RNA significantly inhibited gastric cancer cell proliferation in vitro and in vivo. Overexpression of differentiation antagonizing non-protein coding RNA notably increases gastric cancer cell proliferation. From RNA-seq and gene ontology annotations, we found that differentiation antagonizing non-protein coding RNA influences the gene expression programs in cell metabolic and cycle process. Taken together, our findings suggest that the long non-coding RNA differentiation antagonizing non-protein coding RNA promotes the proliferation of gastric cancer and is a potential prognostic biomarker and therapeutic target in gastric cancer.